2011
DOI: 10.21236/ada543111
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Milled Nanocrystalline Tungsten Powders

Abstract: Approved for public release; distribution unlimited.ii REPORT DOCUMENTATION PAGE Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…One grain may grow into another whilst being consumed from the other side to become a bigger grain. The grain growth has been observed previously in the case of nanostructured tungsten prepared by powder metallurgy[35].Butler et al indicates that the thermal stability changes significantly based on milling conditions. They observe a gradual increase in grain size throughout the temperatures range from 1073 to 1673 K, while a reduced in the grain growth from 1273 to 1473 K depending on sintering process.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…One grain may grow into another whilst being consumed from the other side to become a bigger grain. The grain growth has been observed previously in the case of nanostructured tungsten prepared by powder metallurgy[35].Butler et al indicates that the thermal stability changes significantly based on milling conditions. They observe a gradual increase in grain size throughout the temperatures range from 1073 to 1673 K, while a reduced in the grain growth from 1273 to 1473 K depending on sintering process.…”
mentioning
confidence: 53%
“…In the case of the nanocrystalline tungsten, the activation energy shows a strong correlation to the grain size. It has been reported to change from 400 to 900 kJ/mol for powder samples with a grain size of 135 and 650 nm, repectively [35]. Butler et al [43] report a similar correlation.…”
Section: Annealed Atmentioning
confidence: 80%
“…A high value of the sintering activation energy indicates low thermal stability, which causes a reduction in grain boundary mobility. An increase in the apparent sintering activation energy for coarse W powders beyond that for grain boundary diffusion indicates that a significant portion of the energy is being used to change the structure of the material without contributing to the densification process [45]. Therefore, fine W powders with the particle size of 0.4 μm are the best ones to be sintered up to 1700°C under a pure H 2 atmosphere, as these powders are highly thermally stable compared with the other ones.…”
Section: Evolution Of Activation Energy During Sintering Processmentioning
confidence: 99%
“…The first is top-down via severe plastic deformation (SPD) to reduce the grain size of a monolithic component, such as equal-channel angular processing (ECAP), high pressure Additions of grain growth inhibitors are advantageous, as well as high pressure-assisted sintering with short thermal exposure, both of which could assist in simultaneously obtaining high density and fine grain size [8][9][10][11][12]. For example, Wahlberg et al reported a synthesis method which could control particle growth to produce uniformly yttrium doped nano-sized tungsten powders [10].…”
Section: Introductionmentioning
confidence: 99%